Tick infestation masquerading as a nodule in the eye lid - Shrestha, Nirsara; Shrestha, Sangeeta; Shrestha, Arjun; Suwal, Barsha; Sharma, Samata (Nepalese Journal of Ophthalmology, 2020)
Introduction: Ticks are ectoparasites which can lead to various blood borne diseases. Tick bite may resemble pigmented nevi, mole or nodule resulting a diagnostic dilemma. Tick bite in eye lid is rare and this case report describes tick bite in lower eye lid mimicking a traumatized pigmented nodule where the tick was identified only on magnification and was successfully removed mechanically. Case: A 61-year-old man presented to the eye out patient department with a sudden and painful black pigmented lesion on the right lower lid for four days. The tick was manually removed with forceps. Conclusion: This case report explains the need for a high index of suspicion as tick bite in sudden or recent onset pigmented lesions especially in endemic areas.